Cognitive model of the national financial market: creating process and prospects for assessing the security of its functioning - E. A. Loktionova (Финансы: теория и практика, 2022)
The subject of the research is the Russian financial market. The aim of the study is to develop a cognitive model of the Russian financial market to assess the security of its functioning. The relevance of the study is due to the need to assess the reaction of the national financial market to various exogenous and endogenous stressors in the face of growing geopolitical tensions and the emergence of new artificial restrictions on the access of domestic investors to foreign sources of capital. The belonging of modern financial markets to complex adaptive systems consisting of elements and relationships, the formal description of the dynamics of which is very problematic, determines the advisability of using cognitive analysis and modeling methods in the process of assessing the safety of their functioning. A feature of the study is that when building a cognitive model of the national financial market, the author uses as the main elements not individual actors of the financial market, but macroeconomic aggregates that characterize the state of the financial market and the economy as a whole. The actor-network structure of the national financial market presented in this way makes it possible to consider the high degree of interpenetration of the financial and real sectors, which is characteristic of the modern economy. The novelty of the paper lies in the development of tools for analyzing the dynamics of the financial market as a result of constructing a methodological framework for studying the security of its functioning based on cognitive modeling. The developed cognitive model shows how the identified macro-aggregates change as a result of the spread of a positive or negative impulse, allowing to highlight the critical factors ensuring the sustainable functioning of the financial market. The author concludes that in the case of a balanced state of the considered macroeconomic aggregates, the existing hierarchical structure of the Russian financial market makes it possible to localize and neutralize crisis phenomena of an endogenous nature. At the same time, within the framework of the existing networks of the interaction of the financial market, exogenous stress impulses will intensify and lead to a violation of its effective performance of the function of capital circulation. The practical significance of the research results lies in the ability to determine the stabilizing processes and mechanisms operating in the economy as a whole and in the financial sector in particular, and in their absence, to identify the possibilities for their design that can increase the systemic security of the functioning of the country’s financial market.